The Cytopathic Effect of Different Toxin Concentrations From Different Clostridioides difficile Sequence Types Strains in Vero Cells - Hamo, Zohar; Azrad, Maya; Fichtman, Boris; Peretz, Avi (Frontiers in Microbiology, 2021)
Clostridioides difficile is one of the leading causes of healthcare-associated diarrhea, with severity ranging from mild, self-limiting disease to life-threatening toxic megacolon. C. difficile infection (CDI) pathogenesis is mediated by the TcdA and TcdB toxins. This work aimed to draw correlations between toxin levels, bacterial strains and disease severity in 63 CDI patients. C. difficile typing was performed by multi-locus sequence types (MLST). Toxin concentrations were measured using the TOX A/B test. In addition, cell cytotoxicity assay was performed following Vero cells exposure to stool extracts (24h). The most prevalent sequence types (ST) were ST2, ST4, ST6, ST13, ST37, ST42, and ST104, with highest toxin levels produced by ST42 and ST104 (302.5 and 297.1 ng/ml, respectively). These strains had a stronger cytopathic effect on Vero cells as compared to strains with lower toxin concentrations (p < 0.001), as manifested by lower cell counts and higher percentages of cell rounding and adhesion loss. Although no association was found between ST, toxin concentrations and disease severity, a diverse in vitro effects of different STs on the viability and activity of Vero cells was observed. These findings suggest that disease severity is affected by both host immune responses and by bacterial characteristics.